2020
DOI: 10.1021/acsami.0c06301
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Functionality of Dual-Gate Organic Transistors Based on Semiconducting/Insulating Polyblend-Induced Asymmetric Charge Modulation Layers

Abstract: Dual-gate organic thin-film transistors (DG-OTFTs) with enhanced functionality, including large current enhancement behavior, highly efficient threshold voltage controllability, and self-contained dual-mode logic gate features, are reported. These DG-OTFTs are based on a semiconducting/insulating polyblend-based active layer with asymmetric top and bottom charge modulation layers (atb-CMLs). The atb-CMLs are automatically generated through the preparation of multilayer stacks of phase-separated semiconducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Normally, this low level of binding energy has only been found for the dissociation of inorganic excitons, and thus commonly lesser free charge carriers are available in organic semiconductors. The ɛ r of the P3HT film is commonly around 3.5, [51] which was used to calculate the corresponding E b value. The obtained E b value is about 0.61 eV, which is six times larger than that in the environment with the ɛ r = 21.…”
Section: The Activation Of Photocatalytic Hydrogen Evolution Reaction...mentioning
confidence: 99%
“…Normally, this low level of binding energy has only been found for the dissociation of inorganic excitons, and thus commonly lesser free charge carriers are available in organic semiconductors. The ɛ r of the P3HT film is commonly around 3.5, [51] which was used to calculate the corresponding E b value. The obtained E b value is about 0.61 eV, which is six times larger than that in the environment with the ɛ r = 21.…”
Section: The Activation Of Photocatalytic Hydrogen Evolution Reaction...mentioning
confidence: 99%
“…Many studies have demonstrated that OSCs can be applied to light-emitting diodes, thin film transistors (TFTs), solar cells, memories, and sensors. Among various applications of OSCs, organic TFTs (OTFTs) can be widely used in many types of devices or systems. OTFTs act as basic units, such as drive and switch devices in electronic circuits. The combinations of different OTFTs form various logic gates. OTFTs can also work as nonvolatile memory devices. ,, Moreover, because of the feature of signal amplification, OTFTs can be appropriately used as sensing devices, such as photosensors, gas sensors, and biosensors. ,, Recently, the introduction of the internet of things leads to the increased requirement of smart wearable devices. Smart wearable devices usually contain various types of sensors, specifically photosensors for the use of image recognition, light control, and snapping.…”
Section: Introductionmentioning
confidence: 99%